Sarah Osborn's world: the rise of evangelical Christianity in early America - Brekus, Catherine A. (New directions in narrative history, 2013)
Memoir -- Never despair -- Name of Christ -- Afflicted low condition -- Amazing Grace -- Diaries and letters (1744-1796) -- Lord gave, and the Lord hath taken away (1744) -- No imaginary thing (1753-1755) -- Pinching poverty (1756-1758) -- Love thy neighbor (1759-1763) -- Jordan overflowing (1765-1774) -- Latter days (1775-1787) -- Open vision (1796) -- Protestant saint